Peningkatan Pengetahuan Tentang Rimpang yang dapat Dimanfaatkan sebagai Obat Herbal di Desa Bato Kota Pariaman - Arive, Arivetullatif; Azuxetullatif, Azuxetullatif; Sulastri, Sulastri; Fathiah, Fathiah; Putri, Maharani; Junaidi, Junaidi (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2025)
Efforts to increase public knowledge about rhizome plants (ginger, turmeric and lemongrass) which can be used as herbal or natural medicine. Opening the insight of the people of Bato village in increasing their immune system to reduce the increase in degenerative diseases such as diabetes, hypertension and cholesterol. We carry out community service activities for Bato Village PKK mothers. In this activity, bioactive compounds from ginger, turmeric and lemongrass rhizomes were introduced and their benefits for the body. Overall, community service activities were able to run well and were conducive, this can be seen from the many questions asked by PKK women who gained new knowledge about the benefits of rhizome plant